Effect of Photoperiod on Estrus Cycle and Reproductive Organs in Female African Giant Rat (Cricetomys Gambianus: Waterhouse) - Lavoisier, Fonou Tadiesse; Constant, Fopa Foda; Bertin, Vemo Narcisse; Tsambou, Martine Astride; Severin, Fonkem; Mbogne B, Takam; Augustave, Kenfack (International Journal of Sustainable Agricultural Research, 2021)
African giant rat is a prolific animal in its wild condition. Therefore, in captivity, the decrease in productive performances may be due to photoperiod under which they are submitted. This research was carried out to evaluate whether photoperiod affects estrus cycle and reproductive organs in female African giant rat (AGR). Twenty-eight matured female AGR were randomly assigned to four lighting conditions (Light / Dark): 0 L/ 24 D, 12 L/ 12 D, 18 L/ 06 D and 24 L/ 0 D. Animals were individually housed and had free access to food and water. Daily, vaginal smears were taken and observed under a microscope to determine estrus cycle length. After four weeks, twelve animals were sacrificed and sexual organs were collected and weighted. Results showed that in AGR, the length of estrus cycle ranged between 5.5 and 6.4 days. However, this estrus cycle duration showed an upward (p>0.05) trend with a decreasing photoperiod. The weight of ovary and uterus was significantly (p<0.05) low in animals continuous enlightened compared to other treatment groups. Uterus length have dropped by 13.94%, 17.81 % and 9.50 % in animals exposed to 12 h, 18 h and 24 h of light per day respectively compared to those bred in dark condition. Regarding above results, AGR has a regular estrus cycle and the variation of photoperiod does not have effect on the duration of estrus cycle but it is detrimental for reproductive organs.